Hyperphosphorylation of Tau Protein in Hippocampus of Central Insulin-Resistant Rats is Associated with Cognitive Impairment - Dantao Peng; Xiuqing Pan; Ju Cui; Yueqin Ren; Jiewen Zhang (Cellular Physiology and Biochemistry, 2013)
Background: Alzheimer's disease (AD) is one of the most common neurodegenerative diseases. Peripheral insulin resistance increases the risk for memory impairment and the development of AD. Objective: This study aims to assess changes in cognitive functions and the level of hyperphosphorylated tau proteins in central insulin-resistant rats. Methods: An in vivo central insulin-resistant (CIR) animal model was generated through intracerebroventricular injection of streptozotocin (STZ) into insulin-resistant (IR) rats that were induced by feeding a high-glucose/-protein/-fat diet. The Morris water maze test was used to assess changes in cognitive functions, pathological changes in the cornu ammonis 1 (CA1) region of the hippocampus were detected by immunohistochemistry, and the phosphorylation levels of tau proteins at specific sites were determined by Western blot analysis. Results: The escape latency time in the Morris water maze test was significantly prolonged; the number of phosphorylated tau proteins in the CA1 region of the hippocampus was significantly increased; and the phosphorylation levels of tau proteins at Ser199, Thr205, Thr212, Thr217 and Ser396 were significantly elevated in the CIR group compared with the IR and control groups. Conclusion: This study provides direct evidence that CIR plays an important role in AD pathogenesis by facilitating tau hyperphosphorylation.